Econometric Inflation Targeting - Gunnar Bardsen; Eilev S. Jansen; Ragnar Nymoen (Norges Bank, 1999)
Inflation targeting makes the Central Bank's conditional inflation forecast the operational target for monetary policy. Successful inflation targeting requires knowing the transmission mechanisms to inflation from shocks as well as instruments. The econometric implications are that the exogeneity assumptions of a conditonal forecasting model of inflation are crucial to the quality of the forecasts. We advise that econometric inflation forecasting should be based on a core wage-price model, grafted into a wider set of equations that capture the important transmission mechanisms between inflation and policy instruments (interest rate, exchange rate) as well as between inflation and shocks to the economy. We develop a model of the inflation process in Norway by estimating a dynamic model of wages and prices, supplemented with marginal models of the transmission mechanisms of shocks and instruments. The exogeneity assumptions are tested and accepted. Finally, we demonstrate the model responses to shocks and corresponding changes in monetary instruments and examine the suitability of the full system for inflation forecasting.
hdl:11250/2500538
Keywords: C3; C5; E3; E5; J3; 330; inflation targeting; monetary policy; wages and prices; cointegration; dynamic modelling